Binder Parameter in a Generalized Two-dimensional XY Model - Xuan Nui, Duong; Thi Bach Yen, Truong; Huu Cuong, Nguyen; Bich Linh, Luu; Thi Toan Thu, Bui; Vu Cam Binh, Nguyen; Thi Huyen, Nguyen; Ngoc Anh, Nguyen; Viet, Dao Xuan (VNU Journal of Science: Mathematics - Physics; Vol 40 No 1DO - 10.25073/2588-1124/vnumap.4868, 2024)
We performed Monte Carlo simulation for a two-dimensional generalized XY model and calculated the magnetic and nematic Binder parameters. The phase diagram is re-examined based on these Binder parameters, demonstrating their power in studying generalized XY models. The Binder parameter has distinctive behaviors, resulting in different types of phase transition. More importantly, the magnetic Binder parameter gives more insights into the tricritical region where the Kosterlitz-Thouless, Ising, and 1/2 Kosterlitz-Thouless (KT) transition lines meet. It shows signatures for the intermediate region starting from the tricritical point, where the transition line is neither the same physics as the Ising transition below nor the KT transition far above the tricritical point.